2023
DOI: 10.47134/ijsl.v3i2.108
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Disaster Education to Students of Senior High School Using Role Playing Learning Model

Abstract: The aims of this study are 1) to analyze earthquake disaster education in State Senior High School 1 Karangreja, using a role-playing learning model.; 2) to analyze the knowledge and students’ attitude in dealing with earthquakes. The population of this study was all students of State Senior High School 1 Karangreja. State Senior High School 1 Karangreja is located on the slopes of Mount Slamet, making it prone to volcanic earthquakes. Disaster education for students is very needed. This will allow the student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
1
0
1
Order By: Relevance
“…Asiah et al emphasized the use of effective methods, including role-playing, along with exercises, especially in teaching critical situations [ 16 ]. Wiesefer and colleagues found that the benefits of role-playing, such as developing communication and active listening skills, fostering enthusiasm and motivation in learners, promoting collaboration, and facilitating group discussions and emotional experiences, were evident [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asiah et al emphasized the use of effective methods, including role-playing, along with exercises, especially in teaching critical situations [ 16 ]. Wiesefer and colleagues found that the benefits of role-playing, such as developing communication and active listening skills, fostering enthusiasm and motivation in learners, promoting collaboration, and facilitating group discussions and emotional experiences, were evident [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data tersebut tentunya menjadi perhatian khusus mengingat warga di sekitar daerah rawan bencana mestinya diberikan pelatihan atau minimal pernah mengikuti pelatihan mitigasi bencana. Minimnya, warga masyarakat dan warga sekolah di daerah rawan bencana dalam mengikuti pelatihan mitigasi bencana juga terjadi di Aceh dan Purbalingga (Syamsidik et al, 2021), (Asiah et al, 2023). Pentingnya edukasi dan praktek simulasi mitigasi bencana bagi warga di daerah rawan bencana telah dikaji oleh riset terdahulu dimana hasil riset tersebut menunjukkan bahwa ada peningkatan pengetahuan dan kesiapsiagaan warga pasca mengikuti kegiatan simulasi.…”
Section: Monitoring Dan Evaluasiunclassified